64-slice computed tomography as an adjunct to aortography in suspected iatrogenic aortocoronary dissection. (August 2011) - Dorman, Stephen; Sorbets, Emmanuel; Serfaty, Jean-Michel; Juliard, Jean-Michel
Iatrogenic aortic dissection is an uncommon but potentially fatal complication. We present a case of iatrogenic coronary dissection following percutaneous coronary intervention to the right coronary artery. Aortography initially suggested coronary dissection complicated by type A aortic dissection, however, 64-slice computed tomography excluded classical aortic dissection and instead demonstrated widespread pericardial extravasation secondary to coronary perforation/rupture. This article reviews the pathophysiology, diagnosis and management of aorto-coronary dissection.